Çocuklarda Nozokomiyal Enfeksiyonlar İçin Risk Faktörleri - Çataklı, Tülin; Yöney, Aysel (Journal of Contemporary Medicine, 2021)
ABSTRACTAim: To determine the frequency of nosocomial infections developed within a year in patients admitted to a tertiary pediatric hospital. Materials and Method: The patients who have been hospitalized at Dr Sami Ulus Children Hospital in a one-year period between February 1996 - February 1997 and diagnosed ‘nosocomial infection’ during their follow up were included in this study. The ‘nosocomial infection’ diagnosis used was based on Center for Disease Control (CDC) diagnostics criteria. Clinical findings were recorded besides laboratory and imaging data.ResultsIn one-year period under consideration, a total number of 3420 patients were hospitalized. Nosocomial infection was detected in 9.1% (n=311) of these patients. 28.6% (n=89) of them were acute gastroenteritis, 23.4% (n=73) were urinary tract infection and 25.4% (n=79) were sepsis. The most common etiologic agents were K. pneumoniae (.3), Salmonella spp. (.0) and E. coli (.4). 77.8% of the patients with nosocomial infection were younger than one year old. In patients with urinary tract infection, 28.7% had urethral catheterization. Nosocomial infection was being observed after 16.9±10 days of hospitalization. 12.2% (n=38) of the patients with nosocomial infection have died. Inadequacy of professional staff, insufficient number of nurses per patient and failures in hand washing were thought to be the risk factors in the development of nosocomial infection.Conclusion: Nosocomial infection is an important cause for mortality and morbidity in pediatrics clinics. The most important steps in the efforts to decrease nosocomial infection frequency may be listed as the surveillance, detection of the problems and taking corresponding precautions to take the nosocomial infection under control.Keywords: Nosocomial infection; Child; Risk factors.ÖZAmaç: Üçüncü basamak çocuk hastanesine bir yıl içinde başvuran hastalarda gelişen hastane enfeksiyonlarının sıklığını belirlemek.Gereç ve Yöntem: Dr. Sami Ulus Çocuk Hastanesi'nde Şubat 1996 - Şubat 1997 ...